Buddha is hiding : refugees, citizenship, the new America - Ong, Aihwa (California series in public anthropology, 2003)
This work tells the story of Cambodians whose route takes them from refugee camps to California's inner-city and high-tech enclaves. We see these refugees becoming new citizen-subjects through a dual process of being made and self-making, balancing religious salvation and entrepreneurial values.